Legal Problems of Data Base Technology - David J. Dixon (Washington University Law Quarterly, 1977)
As computers become an integral part of court and business procedures, conflicts will arise that cannot be readily solved by traditional legal theories. Lawyers, acting as planners and advisers as well as advocates, must anticipate the potential problems presented by computers and provide a rational basis for their ultimate solution. In this Article, Judge David Dixon discusses the potential confidentiality problems created when a court uses a computer to collect information on the court’s operational efficiency. He notes that recording court opinions on computers may result in inaccuracies in addition to general problems of attributing and protecting ownership of data bank and program design. In conclusion, he urges the legal profession to design new protections to satisfy the unique requirements of computer use by private entities and the courts.
Keywords: Computing and the Law